The results of judo fights during the 2018-2019 World Championships - Sulecka, B.; Adam, M.; Wolska, B. (Baltic Journal of Health and Physical Activity, 2020)
Background: The aim of the study was to analyze female and male competitors` results of judo fights during the 2018-2019 World Championships in the light of the new regulations of sports fights. Material and methods: The research material involved the recording and analysis of athletes` fights during the 2018 World Judo Championships in Baku (Azerbaijan) and the 2019 World Judo Championships in Tokyo (Japan). In total, 1,659 fights were analyzed, including 997 bouts in the group of men and 662 bouts in the group of women. The collected material allowed analyzing the ways of resolving bouts by competitors in extreme weight categories, bouts completed in the regular time and in the extra time, and fights fought in qualifying rounds and in the medal zone (medal fights). Results: There were no clear differences in the ways of resolving the bouts fought in the groups of women and men. In the group of heavy-weight categories, a certain predominance of attacks completed by ippon was found, while in the group light-weight categories by waza ari. Also fights that were completed in the regular time were most often resolved by direct ippon and two waza ari = ippon, while the fights completed in the extra time were definitely more often completed by waza ari or disqualification - hansoku make. During the elimination fights, competitors more often than during medal fights resolved bouts by disqualification, while competitors fighting for medals more often won through waza ari than the competitors fighting in the qualifying rounds. Conclusions: The most important differences were observed in the results of fights completed in the regular time and in the extra time of fighting. The groups of athletes of light- and heavy-weight categories differed in the number of points obtained by ippon and waza ari. In the elimination and medal fights, the number of obtained waza ari was the most differentiating factor. During direct fights for medals, competitors resolved bouts the least often by hansoku make.